Model Hidrologi Runtun Waktu Untuk Analisis Hujan Aliran Menggunakan Metode Gabungan Model Transformasi Wavelet Ihacres (Studi Kasus Sub DAS Lubuk Bendahara) - As, Andyca Putra; Suprayogi, Imam; Fauzi, Manyuk (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The IHACRES model application has been successfully applied in Indonesia. The existence of this success, it is necessary to further develop an approach to improve the correlation coefficient at the phase of calibration, verification, and simulation by combining the wavelet transformation - IHACRES model by taking a case study in Siak Hulu sub-watershed, Riau Province. Wavelet transformation method in this research has the advantage to decomposed and reconstructed in processing a raw data of time series to increased model performance. The output of wavelet transformation model would be use as IHACRES model input. Wavelet family which suitable for modeling are Haar and Biorthogonal wavelet. This research used the variety of length data that grouped into scheme 1 until scheme 8. The results showed that the best scheme in calibration phase for IHACRES model is scheme 2 (two year calibration) with a correlation value of 0.549. Scheme 2 used for wavelet transformation - IHACRES combine analysis. At wavelet transformation – IHACRES phase, the best calibration value was the used of Haar wavelet level 1 for rainfall and temperature data with a correlation value of 0.561. The best verification and simulation phase used Haar wavelet level 1 to input the data of rainfall and discharge. The result of verication phase valued at 0.674 and simulation was 0.737 which categorized as strong correlation. According to result of reserch, the use of wavelet transformation – IHACRES provides increased performance model, if compared with the IHACRES model. Keywords: Siak Hulu sub-watershed, Wavelet Transformation, IHACRES.